2005
DOI: 10.1007/s10620-005-3061-3
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Risk Factors in the Turkish Community

Abstract: Hepatitis C virus (HCV) is the most common chronic blood-borne infection in the worldwide. This infection is often insidious and one-half of infected patients are asymptomatic. Determination of risk factors for HCV transmission is very important. The aim of this study was to assess the risk factors, transmission to spouses and children for HCV infection in Turkish population. One hundred and fifty-one patients with chronic hepatitis C and 151 control cases were investigated for the probable risk factors of HCV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
11
1
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 21 publications
3
11
1
3
Order By: Relevance
“…These findings were similar to other study which detected a high prevalence of (22.4%) anti-HCV seropositivity following dental surgery [23]. Similar studies conducted in Pakistan, Turkey, Morocco, and Italy had reported that dental procedure was one of the major risk factor for HCV transmission [1,4,11,24]. Moreover Ali et al, (2011) indicated that dental procedure is one of the major source of exposure for HCV transmission (39.7%) followed by injections (16.6%) and surgical procedures (16.6%) [24].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These findings were similar to other study which detected a high prevalence of (22.4%) anti-HCV seropositivity following dental surgery [23]. Similar studies conducted in Pakistan, Turkey, Morocco, and Italy had reported that dental procedure was one of the major risk factor for HCV transmission [1,4,11,24]. Moreover Ali et al, (2011) indicated that dental procedure is one of the major source of exposure for HCV transmission (39.7%) followed by injections (16.6%) and surgical procedures (16.6%) [24].…”
Section: Discussionsupporting
confidence: 91%
“…Probabilities due to sexual and interfamilial transmission are somehow low. In addition, tattoo may also consider as suspected factors in the transmission [4]. Transmission of HCV has been mainly related to intravenous drug use since blood products transmission has decreased in most developed countries [5].…”
Section: Introductionmentioning
confidence: 99%
“…5 In stu di es from Tur key, the rate of IV drug abu se as a risk factor for HCV trans mis si on was very low. 6,7 In vi ew of all the se facts, this ca se con trol study was de sig ned to de ter mi ne the risk fac tors of he pa ti tis C in fec ti on in To kat, a pro vin ce lo ca ted in the middle-in te ri or Black Se a Re gi on of Tur key.…”
mentioning
confidence: 99%
“…Yil di rim et al 6 com pa red 151 HCV po si ti ve pa ti ents who app li ed to Is tan bul Uni ver sity, Cerrah pa sa Fa culty of Me di ci ne Hos pi tal with the control gro up in terms of risk fac tors. In that study, it was de ter mi ned that the fol lo wing risk fac tors were ob ser ved sig ni fi cantly mo re com mon than the con trol gro up: sur gery, fre qu ent den tal ca re, den tal ex trac ti on, blo od tran fu si ons, mul tip le-part ners and se xu al in ter co ur se.…”
mentioning
confidence: 99%
See 1 more Smart Citation